Exploring AI's Ethical Impact on Teacher-Student Dynamics in English Language Learning - Aly, Abdul Hamid; Setiadi, Samsi; Zuriyati, Zuriyati (Journal La Edusci, 2025)
This study explores the impact of Artificial Intelligence (AI) in English as a Foreign Language (EFL) learning, aiming to understand how AI influences teacher-student dynamics, the ethical challenges involved, and students' perceptions of AI in the classroom. The research adopts a qualitative ethnographic approach, engaging with 220 students and 58 lecturers from universities in the Jabodetabek region. Data were collected through participant observation, in-depth interviews, and document analysis, focusing on the integration of AI tools such as ChatGPT and Gamma. Thematic analysis was employed to identify key patterns in teacher-student interactions, ethical concerns, and student engagement. Findings indicate that AI enhances student autonomy and learning personalization while reducing the direct communication between teachers and students. Ethical challenges identified include data privacy concerns, the risk of over-dependency on AI, and the potential dehumanization of the learning process. From the student perspective, AI reduces language anxiety and increases engagement through flexible, personalized learning experiences, but some students miss the emotional connection traditionally provided by human teachers. The study concludes that while AI offers significant educational benefits, careful consideration must be given to maintaining ethical standards and human-centered teaching practices. Future research should focus on integrating AI tools that support not only cognitive learning but also emotional and ethical aspects to ensure balanced educational outcomes.